The hidden drivers: Unraveling the impact of density, moisture, and scale on Hermetia illucens rearing. - Anjani Nayak; Patrick Klüber (PLoS ONE)
The black soldier fly (Hermetia illucens) is a saprophagous insect known for bioconverting organic waste, potentially offering environmental benefits, such as contributing to waste reduction and nutrient cycling. The performance of larvae varies significantly with factors substrate moisture, larval density, and scale of production. Three experiments were conducted using a mix of spent mushroom substrate (SMS) and chicken feed (CF). In the first experiment, 250 larvae were reared on 100 g dry matter (DM) feed at moisture levels of 65-75%. Results showed that the average individual larval weight, total biomass, and feed conversion ratio (FCR) improved with increased moisture. In the second experiment, 300 and 350 larvae/box were tested at 70% and 75% moisture. The highest average individual larval fresh weight (158.6 mg) was observed at 70% moisture with 250 larvae, while the highest biomass was achieved at 75% moisture with 300 larvae. Finally, different scales (10-2,500 g feed with 25-6,500 larvae) were tested with a similar feeding rate. The highest individual larval weight was recorded at the 100 g scale, with no clear correlation between weight and scale. However, the 50 g scale achieved the highest substrate reduction (33.2%). Overall, this study underscores the need to adjust moisture, density, and scale to nutrient conversion efficiency when using SMS, CF or other diets. The optimal results for the SMS feed mix were observed at 75% substrate moisture, 250 larvae per 100 g DM, and at approximately 2 larvae per cm2.